Redesain Gedung Proyek Pembangunan Klinik SUPERSKIN Semarang Berbasis Information Modelling (BIM) 4D - Farhan Fajrul Falah (Universitas Diponegoro, 2025)
BIM (Building Information Modeling) Based Planning has gained significant traction within the construction industry. Nonetheless, its implementation faces several challenges that require attention. This study aims to pinpoint these challenges, encompassing issues such as a lack of awareness regarding the advantages of BIM, limited compatibility among BIM software, and difficulties in precise data collection and integration. The primary objective of this research is to scrutinize the advantages associated with BIM-based planning, notably focusing on enhanced team collaboration, precision in planning, and optimization of time and resources. The research methodology includes a comprehensive literature review and case studies analyzing the utilization of BIM in construction projects. The findings highlight that planning rooted in BIM can enhance planning efficiency, mitigate design clashes, and enhance the accuracy of cost estimations. The research output comprises Tekla structures design outcomes, SAP planning, and Tekla Structure scheduling.